TERORISME DAN PESANTREN - Zainal Abidin Rahawarin (DIALEKTIKA, 2018)
The position of Islam in the 21st century global politics, distorted and tremendous pressures. There are two important variables that become steriotip the initiators of anti-Islam. First; the revival of Islam in the context of global politics is to build empires of Islam or Islamic caliphate. Second; Abundant natural resources in the Muslim lands into force of development and progress. Both are a potential threat to the West. This is the root of the birth of global war were then packaged in military-political terms as terrorism or in termteori provocative politics with little scientific terms clash of civilizations. Islamic boarding schools as an educational institution Islamispencetak character clerics in Indonesia, has entered the political arena map-terrorism. Pesantren was pure acting in the scholarly study of classical Islam (the yellow book), then developed into Islamic educational institutions modern by combining the study of classical Islamic approach to modern science, began to be positioned as an institution that potentially give birth to thinkers fundamentalist, so it needs to be reduced to its existence, that is by controlling the education system through curriculum. In addition, the boarding school became a potential claim political interests, which at times can be used as a tool popaganda possible interest